THE INFLUENCE OF E-MAIL MARKETING TOWARDS BRAND LOYALTY OF LAZADA.CO.ID - GANA DUWA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this research is to examine the influence of E-mail marketing toward Brand Loyalty Lazada.co.id. In order to know the relationship among E-mail marketing towards Brand loyalty, a simple regression analysis, F-test, T-test, was applied. The samples in this research is 100 people with the criteria that those persons should be customers of lazada.co.id and have gotten email marketing from lazada.co.id. The sampling technique was a purposive sampling with 100 respondents and the research instrument used demographic background, E-mail marketing and Brand Loyaty. The test is using validity test and reability test. The hypothesis testing was using T test to analyze the data to be used in Simple Regression Analysis. There is positive and significant influence of E-mail marketing on Brand LoyaltyKeywords: Email marketing, Brand Loyalty